Evaluasi Formula dan Uji Aktivitas Antibakteri Gel Ekstrak Daun Johar (Cassia siamea L.) dengan Beberapa Perbandingan Gom Arab dan Tragakan Terhadap Staphylococcus aureus - Puspitasary, Kiki; Nur Wijayanti, Anisa; Indarto, Indarto (PC Ikatan Apoteker Indonesia (IAI) Karanganyar, 2023)
Skin infections are caused by bacteria, one of which is the Staphylococcus aureus bacteria, which causes acne. One plant that has antibacterial properties is the johar leaf plant (Cassia siamea L.). This plant contains alkaloids, flavonoids, saponins, and tannins. This study aims to determine the antibacterial activity of johar leaf extract gel preparations. One preparation that is suitable for use with acne is gel. Gel is considered more comfortable to use, causes a cooling sensation when it comes into contact with infected skin, is easier to apply, and spreads well. The research method used is experimental in the laboratory. Johar leaf extract was made into a gel preparation, starting with a preliminary test of the extract against bacteria. The results obtained showed that a concentration of 3% johar leaf extract provided the greatest inhibitory power, namely 23.83 mm. The gelling agents used were gum arabic and tragacanth with a ratio of FI (10%:2%), FII (11%:3%), and FIII (12%:4%). The evaluations of the gel preparations carried out were organoleptic, homogeneity, pH, viscosity, spreadability, and adhesive power. Furthermore, all formulas were tested for antibacterial activity using the well method. The results obtained in this study indicate that the FI, FII, and FIII gel preparations meet the physical requirements for gels. The antibacterial activity test showed that FIII was able to provide the highest inhibitory power, namely 14.18 mm.